2019
DOI: 10.1177/2331502419825610
|View full text |Cite
|
Sign up to set email alerts
|

Bodily Inertia and the Weaponization of the Sonoran Desert in US Boundary Enforcement: A GIS Modeling of Migration Routes through Arizona’s Altar Valley

Abstract: This article conducts geographic information system (GIS) modeling of unauthorized migration routes in the Sonoran Desert in southern Arizona and finds an increase in the ruggedness of terrain crossed by pedestrian travelers throughout time. The modeling of ruggedness incorporates multiple variables that include slope, vegetation, "jaggedness," and ground temperature, and provides an alternative to Euclidian distance as a way of measuring and conceptualizing borderlands space. The data that informs our analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 33 publications
0
11
0
1
Order By: Relevance
“…Although counterintuitive, border crosser mortalities due to heat exposure have increased over time relative to the number of people selecting routes of travel through compensable areas of higher elevations with less sun exposure. Indeed, prior studies have shown that undocumented migration has steadily trended toward more rugged and difficult areas of transit where ambient temperatures tend to be cooler, and that are also characterised by greater access to shade and less sun exposure (Boyce et al, 2019; Chambers, 2020). Such changes in migration routes are a result of a series of ‘Funnel Effects’ associated with PTD (Chambers et al, 2021b; Gokee et al, 2020; Martínez et al, 2021; Rubio‐Goldsmith et al, 2006; Soto, 2018), and they indicate how a lack of water and extended exertion, even in cooler or more ‘hospitable’ environments, can still result in hyperthermia (Boulze et al, 1983).…”
Section: The Evolution Of Boundary Enforcement and Corresponding Patt...mentioning
confidence: 99%
“…Although counterintuitive, border crosser mortalities due to heat exposure have increased over time relative to the number of people selecting routes of travel through compensable areas of higher elevations with less sun exposure. Indeed, prior studies have shown that undocumented migration has steadily trended toward more rugged and difficult areas of transit where ambient temperatures tend to be cooler, and that are also characterised by greater access to shade and less sun exposure (Boyce et al, 2019; Chambers, 2020). Such changes in migration routes are a result of a series of ‘Funnel Effects’ associated with PTD (Chambers et al, 2021b; Gokee et al, 2020; Martínez et al, 2021; Rubio‐Goldsmith et al, 2006; Soto, 2018), and they indicate how a lack of water and extended exertion, even in cooler or more ‘hospitable’ environments, can still result in hyperthermia (Boulze et al, 1983).…”
Section: The Evolution Of Boundary Enforcement and Corresponding Patt...mentioning
confidence: 99%
“…The erection of 'high-security' fencing on the US-Mexico border failed to deter undocumented immigration from Mexico (Masse et al, 2002). While the construction of new fencing in California made unauthorized crossing more difficult, trafficking routes moved to the more dangerous desert areas in Arizona, causing migrant deaths to increase significantly (Boyce et al, 2019;Sundberg, 2013). Contrary to expectations, border fencing encouraged the trafficking economy, and fused drug trafficking with human trafficking (Brown, 2010;Verisk, 2017).…”
Section: An Overview Of Us Border Politicsmentioning
confidence: 99%
“…Instead of deterring potential attempts, these elevated costs often bind migrants to cycles of debt-driven return migration to pay smuggling loans [63]. The weaponization of the borderlands has led to a tragic growth in migrant death and disappearance, with at least 300-500 known migrant deaths recorded near the border every year [23,55,94,100] and a more recent increase in the ratio of deaths to migration attempts [12,92].…”
Section: Expanding Geographies Of Enforcementmentioning
confidence: 99%